Audit of Financial Reporting Documents: Analysis of Process of Determining Materiality - Jurkonienė, Gerda; Stašaitytė, Justina (Buhalterinės apskaitos teorija ir praktika, 2019)
During audit of the financial statements of companies, the auditors use a certain level of materiality to determine both the scope of the procedures and the impact of errors on the representation of the true and fair view of the financial statements. International auditing standards leave wide range of possibilities for interpretation of the materiality process, which often raises the question of how the auditor determines materiality. The purpose of the study is to analyze the materiality process and to create a model of the materiality determination process. Methods of information gathering, comparative analysis, critical evaluation, systematization and interpretation of scientific literature and normative acts of audit are used in this article. After analyzing the materiality determination process, it was found that the materiality process consists of four steps: assessment of determining factors of materiality thresholds, determination of planning materiality, determination of performance materiality and determination of clearly trivial misstatement. Based on the analyzed literature, a model of materiality determination process was developed.
Keywords: financial statements; materiality; audit; planning materiality; performance materiality; clearly trivial misstatement